KAJIAN PARASIT Gyrodactylus sp. PADA LELE DUMBO (Clarias sp.) - , M GIGIH SATRIYO A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this research were to determine characteristic of parasite Gyrodactylus sp., prevalence incidence, spreading infection to several of fish species, biological control, and also effectiveness of chemotherapy with NaCl. The characteristic of Gyrodactylus sp. was analyzed on descriptive from natural infection. Observation of prevalence and incidence were performed from 6 (six) location nursing and growing ponds around DIY and were analyzed using ANOVA. Infection of Gyrodactylus sp., employing of biological control, and treatment with NaCl were conducted at laboratory of Fish Disease under completely randomized design (CRD) and was analyzed using ANOVA. Infection of Gyrodactylus sp. was performed by cohabitation of infected catfish juvenile with mini guppy, synspilum, gourami, tilapia, carp fishes. Employing of biological control were conducted by addition mini guppy, synspilum, and carp fishes into catfish juvenile rearing tanks. The control with NaCl was done with immersion at dose 0